Effect of preheat treatment of milk proteins on their interactions with cyanidin-3-O-glucoside. (May 2018) - He, Wenjia; Mu, Haibo; Liu, Zhenmin; Lu, Mei; Hang, Feng; Chen, Jie; Zeng, Maomao; Qin, Fang; He, Zhiyong
Abstract: In this study, the binding of cyanidin-3-O-glucoside (C3G) to preheated milk proteins β-lactoglobulin (β-Lg) and β-casein (β-CN) at 55–90 °C under pH 3.6 and pH 6.3 was investigated using multi-spectral techniques. Fluorescence quenching spectroscopy data showed C3G quenched milk proteins' fluorescence strongly. Thermodynamic analysis revealed that C3G bound to β-Lg mainly through hydrogen bonding and hydrophobic interactions, and that their binding affinity increased gradually with increasing preheating temperature at pH 6.3, whereas it decreased at pH 3.6. Hydrogen bonding and van der Waals forces played the major roles in the interaction of β-CN with C3G, their affinity decreasing with increasing preheating temperature at both pH values. The combination of C3G and preheated β-Lg at 85 °C had the strongest binding affinity, with a K A of 14.10 (±0.33) × 10 5 M −1 (pH 6.3, 298 K). Preheating of milk proteins did not change their major forces with C3G. Fourier transform infrared spectra (FT-IR) results showed that C3G binding altered the secondary structures of β-Lg and β-CN by reducing the proportion of α-helix and β-sheet structures and increasing the proportion of random coil and turn structures. The structural changes of preheated β-Lg upon C3G binding were more pronounced than that of native β-Lg, while there was little difference between preheated and native β-CN in their structural changes upon C3G binding. These results will be helpful in better understanding the relevance of native and preheated milk protein–C3G interactions to the stability of C3G, and in promoting its application in the food industry as a natural pigment. Graphical abstract: Highlights: C3G binds milk protein mainly via H-bond, Van der Waals and hydrophobic interaction. β-Lg's C3G binding rises with preheat temperature at pH 6.3 but decreases at pH 3.6. Preheating of β-CN decreases its binding with C3G at both pH 3.6 and 6.3. C3G binding alters milk protein structure with a reduction of α-helix and β-sheet. Preheating causes more β-Lg structure changes upon C3G binding, while less for β-CN.